Lifelong smoking status, weight gain, and subsequent risk of major adverse cardiovascular events: Long‐term follow‐up of a middle‐aged Chinese population. Issue 3 (11th February 2022) - Liang, Lirong; Li, Changwei; Liu, Xiaoqing; Zhou, Long; Chu, Shuilian; Zhang, Ruiyuan; Mai, Jinzhuang; Westbrook, Adrianna; Li, Jiachen; Zhang, Di; Zhao, Liancheng; Wu, Yangfeng
Abstract: Objective: The aim of this study was to explore the association of lifelong smoking status with risk of major adverse cardiovascular events (MACE) accounting for weight change in a Chinese cohort. Methods: The cohort of the People's Republic of China‐United States of America (PRC‐USA) Collaborative Study of Cardiovascular and Cardiopulmonary Epidemiology was established in 1983 to 1984, resurveyed during 1987 to 1988 and 1993 to 1994, and followed up to 2005. A total of 5, 849 participants who survived in 1993 to 1994 were classified into never smokers, long‐term quitters, short‐term quitters, short‐term relapsers and new smokers, long‐term relapsers and new smokers, and persistent smokers according to the information on lifelong smoking status collected in all three surveys. The associations of lifelong smoking status with MACE in the subsequent 10 years were explored with Cox proportional hazards models. Results: During a median follow‐up of 10.2 years, 694 participants had MACE. Compared with persistent smokers, the multivariable‐adjusted hazard ratio of developing MACE was 0.83 (95% CI: 0.61‐1.12) for short‐term quitters, 0.75 (95% CI: 0.54‐1.02) for long‐term quitters, and 0.68 (95% CI: 0.54‐0.85) for never smokers ( p trend = 0.001). In comparison, the hazard ratio was 1.03 (95% CI: 0.77‐1.35) for long‐term relapsers and new smokers and 0.78 (95% CI: 0.46‐1.22) for short‐term relapsers and new smokers ( p trend = 0.018). These associations were not significantly altered by further adjusting for weight change in the past 10 years. Conclusions: Lifelong smoking status is significantly associated with risk of MACE. As time duration increased, health benefit to quitters would become close to that of never smokers, and harms to relapsers and new smokers would become close to that of persistent smokers.